2019
DOI: 10.2217/imt-2018-0158
|View full text |Cite
|
Sign up to set email alerts
|

Combination Immunotherapy with IL-4 Pseudomonas Exotoxin and IFN-α and IFN-γ Mediate Antitumor Effects in vitro and in a Mouse Model of Human Ovarian Cancer

Abstract: We have shown that IL-4 fused to Pseudomonas exotoxin (IL-4-PE) is cytotoxic to ovarian cancer cell lines. The antineoplastic properties of IFN-α, IFN-γ and IL-4-PE have been studied and showed some promise in the clinical trials. Here, we investigated whether the combination of IL-4-PE, IFN-α and IFN-γ will result in increased ovarian cancer cell death in vitro and in vivo. Materials & Methods: Ovarian cancer cells were tested in vitro to analyze the cytotoxic effects of IL-4-PE, IFN-α and IFN-γ, and the comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…In a previous study, the combination of IL-4- Pseudomonas exotoxin, IFN-γ and IFN-α resulted in increased apoptotic cell death in ovarian cancer. This mechanism of the synergistic anticancer effect is dependent on IFN-mediated JAK/STAT signaling and the consequent activation of apoptosis-related molecules, including caspase-3, −7 and PARP ( 69 ). These aforementioned studies have provided a theoretical basis for the immunotherapy of cervical cancer and ovarian cancer based on IFN-α.…”
Section: Mechanisms Of Ifn-α-induced Cancer Cell Apoptosismentioning
confidence: 99%
“…In a previous study, the combination of IL-4- Pseudomonas exotoxin, IFN-γ and IFN-α resulted in increased apoptotic cell death in ovarian cancer. This mechanism of the synergistic anticancer effect is dependent on IFN-mediated JAK/STAT signaling and the consequent activation of apoptosis-related molecules, including caspase-3, −7 and PARP ( 69 ). These aforementioned studies have provided a theoretical basis for the immunotherapy of cervical cancer and ovarian cancer based on IFN-α.…”
Section: Mechanisms Of Ifn-α-induced Cancer Cell Apoptosismentioning
confidence: 99%
“…It has been reported that IFN-α and IFN-γ, applied in combination with IL-4 fused to Pseudomonas exotoxin, inhibit tumor growth in an experimental mouse model of human ovarian cancer. The anti-tumor effect was accomplished by the activation of the IFN signaling pathways and the subsequent activation of molecules inducing apoptotic cell death [37]. Characterization of a wide range of tumor-promoting factors and anti-tumor cytokines after ovarian cancer cell expose to HATMSC2-MVs provides information on how they affect the production of functional cytokines and shed light on the mechanism altering the behavior of ovarian cancer cells in response to MV treatment.…”
Section: Effect Of Hatmsc2-mvs On the Secretion Profile Of Ovarian Camentioning
confidence: 99%
“…In contrast, WNT5A knockout mice have upregulated expression of INFg. Although several in vivo and in vitro preclinical studies show an antitumor effect of INFg in ovarian cancer (40)(41)(42), therapeutic trials using INFg have inconsistent outcomes (43). Nevertheless, several trials that incorporate INFg in combination therapy regimens are ongoing in women with ovarian, fallopian tube, and primary peritoneal cancer, including studies to assess the efficacy of combined IFNg with immune checkpoint inhibitors (33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%